2017
DOI: 10.5152/dir.2016.16006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CT vascularization patterns for survival prognosis in patients with hepatocellular carcinoma treated by conventional TACE

Abstract: The vascularization pattern of the largest HCC lesion is helpful for survival prognosis under TACE treatment and therefore has the potential to be used as an additional parameter for treatment stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Miszczuk et al 16 prospectively enrolled 39 liver cancer patients (n = 22, HCC) treated with TACE and they could show, that high Lipiodol coverage on the 24-h post-TACE CT was associated with response to therapy. Lipiodol retention may serve as a surrogate for arterial hyperenhancement 16 , the vascularization pattern of HCC lesions might have prognostic impact 34 and our results provide quantitative corroboration of these findings. In our model, the GLDM feature LargeDependenceHighGrayLevelEmphasis, which depends on higher gray-level values ( https://pyradiomics.readthedocs.io/ ), had the highest predictive impact.…”
Section: Discussionsupporting
confidence: 77%
“…Miszczuk et al 16 prospectively enrolled 39 liver cancer patients (n = 22, HCC) treated with TACE and they could show, that high Lipiodol coverage on the 24-h post-TACE CT was associated with response to therapy. Lipiodol retention may serve as a surrogate for arterial hyperenhancement 16 , the vascularization pattern of HCC lesions might have prognostic impact 34 and our results provide quantitative corroboration of these findings. In our model, the GLDM feature LargeDependenceHighGrayLevelEmphasis, which depends on higher gray-level values ( https://pyradiomics.readthedocs.io/ ), had the highest predictive impact.…”
Section: Discussionsupporting
confidence: 77%
“…Radiomics analysis on arterial phase image was useful for prognosis prediction. This may be explained by that tumor texture patterns in arterial phase imaging could reflect tumor vascularization patterns, which was helpful for prognosis prediction ( 33 ). There may be two reasons explaining the importance of radiomics features from the portal venous images.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in most previous studies laboratory indicators of liver function besides AFP were not found to be significant. In terms of the preoperative pattern of tumor vascularization, Hasdemir et al 30 indicated that the pattern of vascularization of the largest tumor could predict survival after TACE ( P = 0.012). Nevertheless, in our study, this result was not be found.…”
Section: Discussionmentioning
confidence: 99%